Big Stone Gap [videorecording (DVD)] - Trigiani, Adriana (Universal Sudios Home Entertainment, 2016)
Ave Maria Mulligan has lived her whole life in tiny Big Stone Gap, a picturesque coal-mining town nestled in the hollers of southwestern Virginia. When she's not making deliveries from her family's pharmacy to far-flung neighbors, Ave Maria directs the annual outdoor drama festival, keeps chaste company with her longtime beau, Theodore, and exchanges good-natured barbs with local hunk Jack MacChesney.